庄荀心论的丰富内涵 ：“知”和“情”范畴下 的“心”及其修养 = Philosophy of mind in Zhuangzi and Xunzi : the cognitive and emotive aspect of ‘Xin’ and its cultivation - 赖洁思 Lai, Jessy (2018)
在庄子和荀子的思想当中，“心” 具独特的意涵， 单从含义上来看， 它不仅指现在普遍的心脏之义，同时还指思想器官、精神及心绪等等， 涉及的内容极为广 泛， 但目前仍较少有学者关注庄荀，甚至是其他思想家的心论，对“心”缺乏清晰、多面的论述，因此，本文试以“知”、 “情” 的范畴以及“心”之修养的角度来进 一步探讨“心”的涵义。 在探讨庄荀在“知”和“情”范畴下的“心” 当中， 不难发现两者一方面对“心”的界定、特点等各自抱有特殊的诠释， 但在“心”的修养 方面又表现出相似之处， 在同样认为“知”和“情”能对“心”造成影响下， 分别提出“心斋”和“虚壹而静” 的修养方法以使“心”能达到“虚静” 。 另外， 从庄 荀论“心”的深沉涵义来看，仅是以现代普遍的“心” 之义来解读“心”，必然不足以把握其思想的核心，因此， 有必要进一步探讨庄荀的心论， 透过分析两者对 “心”的不同主张与相同理解来彰显“心” 的内容， 使其涵义更加明确， 由此亦有助于将“心”与相关的思想连贯互通。| “Xin”（ also known as “heart-mind”）in Zhuangzi and Xunzi thoughts have unique connotations as meaning-wise, it does not only refer to the literal heart but also mind, spirit and mood etc. The concept of “Xin” encompasses a wide-ranging content in Zhuangzi and Xunzi thoughts, but unfortunately, not much attention had been paid to Pre-Qin philosophers, including Zhuangzi and Xunzi’s “Xin” thus far. Little discussions on “Xin” itself render the lack of a distinctive and comprehensive study of the idea “Xin”. Therefore, this thesis aims to explore the previously not-so-well-defined or neglected basis of “Xin” by studying the cognitive and emotive aspects, as well as the cultivation of Zhuangzi and Xunzi’s “Xin”. Zhuangzi and Xunzi each defines “Xin” and describes its characteristics with their own peculiar ways. Nevertheless, both show similarities in the discussion of cultivating “Xin” which they believed that thinking and feeling, or idea and affect could have an impact on “Xin”, hence put forward the method of XinZhai 心斋 (fasting of “Xin”) and Xu 虚(“empty”), Yi 壹(“unified”), Jing 静(“still”) to cultivate a proper “Xin” of emptiness and stillness 虚静. In conclusion, simply taking “Xin” as “heart” would be insufficient to grasp its implied meaning and thus, there is a need to further analyse “Xin” in Zhuangzi and Xunzi, which would be beneficial to the interpretation of “Xin” and its relevant concepts.